A Development Of Human Resource (HR) Capabilities Through Computer Graphic Design Training To Enhance Student Knowledge At Al- Farabi Integrated Vocational High School (SMK) - Khairul, Khairul; Andri Ismail Sitepu; Darma Putra Lubis; Muhammad Dafa Alfikri; Lamsihar Banjarnahor; Muhammad Hasyim As'ary (Sean Institute, 2024)
This study aims to develop human resource (HR) capabilities through graphic design computer training to improve students' knowledge at Al-Farabi Integrated Vocational School. This training activity is designed as an effort to provide practical skills that are relevant to the needs of the creative industry and information technology. The method used is a quantitative and qualitative approach through observation and evaluation of training results. Training participants are given materials ranging from an introduction to graphic design software to creating creative projects based on digital design. The results of the study showed that this training significantly improved students' understanding and skills in using graphic design software such as CorelDRAW. In addition, students showed increased creativity and analytical skills in developing innovative graphic works. This training also strengthens students' competitiveness in the world of work and the relevance of the school curriculum to industry needs. Thus, developing HR capabilities through graphic design computer training is an effective strategy in improving the quality of education and career opportunities for students in the future.